A putative glucose 6-phosphate isomerase has pleiotropic functions on virulence and other mechanisms in Acidovorax citrulli - Heo, Lynn; Han, Yoobin; Cho, Yongmin; Choi, Junhyeok; Lee, Jeongwook; Han, Sang-Wook (Frontiers in Plant Science, 2023)
Acidovorax citrulli (Ac) is a causal agent of watermelon bacterial fruit blotch (BFB) disease. Because resistance cultivars/lines have not yet been developed, it is imperative to elucidate Ac's virulence factors and their mechanisms to develop resistant cultivars/lines in different crops, including watermelon. The glucose-6-phosphate isomerase (GPI) is a reversible enzyme in both glycolysis and gluconeogenesis pathways in living organisms. However, the functions of GPI are not characterized in Ac. In this study, we determined the roles of GpiAc (GPI in Ac) by proteomic and phenotypic analyses of the mutant lacking GPI. The mutant displayed significantly reduced virulence to watermelon in two different virulence assays. The mutant's growth patterns were comparable to the wild-type strain in rich medium and M9 with glucose but not with fructose. The comparative proteome analysis markedly identified proteins related to virulence, motility, and cell wall/membrane/envelope. In the mutant, biofilm formation and twitching halo production were reduced.We further demonstrated that the mutant was less tolerant to osmotic stress and lysozyme treatment than the wild-type strain. Interestingly, the tolerance to alkali conditions was remarkably enhanced in the mutant. These results reveal that GpiAc is involved not only in virulence and glycolysis/gluconeogenesis but also in biofilm formation, twitching motility, and tolerance to diverse external stresses suggesting the pleiotropic roles of 3 GpiAc in Ac. Our study provides fundamental and valuable information on the functions of previously uncharacterized glucose 6-phosphate isomerase and its virulence mechanism in Ac.